Pelatihan Pembuatan Kertas Indikator Asam Basa Dari Bahan Alam Untuk Siswa SMA - Vinka Nur Octaviani; Lentra Aji Syahputra; Serly Ida Nur Sapfitri; Susegar Khadiningsih; Solfarina Solfarina; Sonny Rohimat (Institut Nalanda, 2023)
Students consider chemistry subjects as abstract and dangerous subjects. Even though chemistry is a very important science and is related to everyday human life. This training activity aims to increase students' knowledge and skills about natural acid-base indicators and their manufacture in the form of litmus-like paper. The training was held in the chemistry laboratory of SMA Negeri 6 Kota Serang on October 13 2023 and was attended by 30 participants. The materials used in making natural indicator paper during the training were purple golden flowers, turmeric, red spinach, bougainvillea, and hibiscus flowers. The test samples included soapy water, toothpaste water, vinegar solution, fizzy drinks, coffee water and baking soda solution. Based on the results of filling in student feedback via the Google Form link, it was found that this activity could increase students' knowledge and skills, as well as change students' perceptions of chemistry to be more positive.